Dynamic Surface Stress Response during Reversible Mg Electrodeposition and Stripping. Issue 13 (1st January 2016) - Ha, Yeyoung; Zeng, Zhenhua; Barile, Christopher J.; Chang, Jinho; Nuzzo, Ralph G.; Greeley, Jeffrey; Gewirth, Andrew A.
Abstract : Through the use of in situ electrochemical surface stress measurements, Mg deposition and stripping processes in electrolytes for Mg batteries are studied. We examine four electrolytes: PhMgCl+AlCl3 /THF, (DTBP)MgCl–MgCl2 /THF, MgCl2 +AlCl3 /THF, and Mg(BH4 )2 +LiBH4 /diglyme. Each of these electrolytes exhibits common surface stress response features, indicating that the mechanisms of Mg deposition and stripping are similar among the different electrolytes. Combining the measurements with density functional theory calculations, each part of the stress-potential curve is assigned to steps in the deposition and stripping reactions. The analysis suggests the following mechanism: (1) Mg 2+ /anion/solvent complexes adsorb on the substrate prior to the deposition; (2) Mg deposits as random nuclei and the deposition continues without a recrystallization process; (3) during the initial stage of Mg stripping, less coordinated Mg(0) is converted to soluble Mg(II) species and to partially oxidized species, MgOx ; (4) as the anodic reactions proceed further, Mg continues to dissolve and MgOx is removed via chemical processes; (5) due to the strong interaction between Mg and the noble metal substrate atoms, the Mg layer directly bound to the substrate are the last to be anodically converted (and desorb).